Successful Repeat Catheter Ablation of Recurrent Longstanding Persistent Atrial Fibrillation With Rotor Elimination as the Procedural Endpoint: A Case Series. (21st December 2015) - SOMMER, PHILIPP; KIRCHER, SIMON; ROLF, SASCHA; JOHN, SILKE; ARYA, ARASH; DINOV, BORISLAV; RICHTER, SERGIO; BOLLMANN, ANDREAS; HINDRICKS, GERHARD
Rotor Elimination as Endpoint for AF Ablations: Background: There remains a lack of consensus regarding the ideal ablation strategy for atrial fibrillation (AF), particularly in patients with persistent or longstanding persistent AF. Given increasing evidence from clinical imaging studies that rotors sustain AF, rotor elimination may be a desirable procedural endpoint. However, there is no description to date of the clinical outcomes using rotor elimination during ablation as the procedural endpoint. Moreover, a series of studies question whether procedural AF termination is a desirable endpoint for ablation after many forms of AF ablation. Methods and Results: We report a single‐center experience of rotor elimination during AF ablation using Focal Impulse and Rotor Mapping (FIRM), describing 20 consecutive patients with case descriptions of 3 patients with recurrent longstanding persistent AF after prior ablation. In all cases, endocardial mapping using a 64‐electrode basket catheter was performed to identify rotors, which were eliminated using radiofrequency catheter ablation. After it was verified that all identified rotors were eliminated, standard ablation consisting of PV isolation was performed. Notably, persistent AF terminated in only 1/20 (5%) patients. However, after a follow‐up of 6 months, single‐procedure freedom from AF was 80% (16/20 patients) with only 1 patient on antiarrhythmic drugs. All three patients in the highlighted series are AF free despite the lack of acute procedural AF termination. Conclusions: Patients with persistent AF including those with unsuccessful prior ablation can be treated successfully by rotor targeted ablation, using the elimination of all rotors rather than acute AF termination as the procedural endpoint.